Where there's smoke there's – litigation: When cigarettes and CSR clash. Issue 6 (11th May 2015) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – The case study illustrates the complex paradigm that interlinks economic and human rights obligations of states on one side of the spectrum and property rights and social responsibilities of tobacco companies on the other. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.